Genotoxicity assessment of TiO2 nanoparticles in SH-SY5Y cells: suitability of the cytokinesis-block micronucleus test - Fernández-Bertólez, Natalia (2022)
Objective: to determine whether Cyt-B could interfere with micronuclei (MN) induction by TiO2 NP in human SH-SY5Y cells, as assessed by CBMN test.